A new mayfly species of Rhoenanthus (Ephemeroptera: Potamanthidae) from Peninsular India - Balasubramanian, Chelliah; Muthukatturaja, Marimuthu; Anbalagan, Sankarappan (Zootaxa, 2019)
A new mayfly species, Rhoenanthus (Rhoenanthus) tungaiensis sp. nov. is described and characterized at the larval stage by fore tibiae relatively long with dense hair like setae on dorsal and lateral surface, male compound eyes large, mandibular tusks 0.8 times longer than head length, segment I of maxillary palpi 1.7 times longer than segment II, fore femur 2.9 times longer than its greatest width, gill III with 46–48 marginal fibrillae on lateral margin of dorsal lamellae and 35–37 on ventral lamellae. At the imaginal stage, the new species can be separated by inverted bell shaped markings on terga, purplish brown intercalaries in forewings, costal cross veins reddish brown and infuscated, MP2 connected to CuA basally.